Life satisfaction of the elderly in Phukhiao District, Chaiyaphum Province, Thailand - Itabashi S (2012)
As Thailand is becoming an aging society, the well-being of the elderly should be one of the important concerns. This cross-sectional descriptive study examined life satisfaction and its related factors of the elderly in Phukhiao district, Chaiyaphum province, Thailand. Participants in the study consisted of 203 local residents aged 60 years old or over living in Phukhiao district. Interviews were conducted by local nurses and the researcher utilizing a structured questionnaire in order to collect data in January 2010. The questionnaire addressed sociodemographic characteristics, Buddhist values, mindfulness, loneliness, and life satisfaction. The participants were mainly female. Their median age was 66 years old. Most of participants reported high scores on Buddhist value, mindfulness, loneliness, and life satisfaction. Pearson’s correlation between Buddhist values (r = .27, p < .01), mindfulness (r =.37, p < .01), loneliness (r = .27, p < .01) and life satisfaction revealed a significant relationship. Multiple regression demonstrated that Buddhist values, mindfulness, and loneliness were significant predictors for life satisfaction of the elderly. In conclusion, Buddhist values, mindfulness and loneliness were positively associated with life satisfaction of the elderly. However, further study is needed to investigate mechanisms of Buddhist values and mindfulness to increase life satisfaction. It is also recommended that in order to help the elderly they should be encouraged to participate in Buddhist activities to promote their well-being.